G122 Safety Netting Behaviour of Primary Healthcare Professionals For Acutely Sick Young Children: A Qualitative Study. (4th June 2013) - Jones, CHD; Neill, S; Lakhanpaul, M; Roland, D; Thompson, M
Abstract : Aims: Acute illness is a frequent reason for consultation in primary care and an important cause of child morbidity and mortality. Healthcare professionals cannot correctly diagnose 100% of childhood illnesses at first consultation, so safety netting is used to extend the consultation and provide parents with information and resources to re-attend if necessary. UK childhood deaths from illnesses presenting to primary care exceed rates elsewhere in Europe, and safety netting has been introduced as a NICE quality standard for bacterial meningitis and meningococcal septicaemia; yet there is no standardised safety netting procedure. We aimed to explore the safety netting behaviour of frontline UK healthcare professionals for parents of acutely sick children under 5-years-old, including frequency, content, mode of delivery, and consistency. Methods: We conducted semi-structured focus groups and interviews with 16 doctors and nurses from general practise, emergency department and out-of-hours settings in the East Midlands, as part of the ASK SNIFF (Acutely Sick Kids, Safety Netting Intervention for Families) project. Data were analysed according to the grounded theory approach. Results: The content and delivery of safety netting was not consistent within or between organisations, whether it was written or verbal: "we've probably all got our favourite patient information leaflets that we give… not at the moment standardised across the practise" (GP surgery doctor); "I know what I say but you know, do we all say the same thing?" (Paediatric ED doctor). Factors influencing safety netting provision included perceived parental anxiety and confidence, healthcare professional parental status and experience, and time. Participants highlighted difficulty in knowing how often safety netting occurs, whether it is understood by parents, and its effectiveness: "often they'll nod their heads and say yes I understand everything you say and walk off and they might have no idea what we've just said" (Regular ED nurse). Other limitations were the broad, nonspecific nature of childhood illnesses, and parental difficulty interpreting information. Conclusion: Healthcare professionals lack standardised methods of safety netting. Addressing this gap in the management of acutely sick children may have potential to improve the efficiency of acute children's services, and reduce avoidable morbidity and mortality.